Unveiling the Macro-Micro Paradox: A Hermeneutic Phenomenology of Pre-Service English Teacher’s Digital Praxis in a Micro-Class of a Rural Indonesian Islamic College - Ayu Meiratnasari; Ema Wilianti Dewi (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2026)
The rapid growth of Generative Artificial Intelligence (GenAI) has changed how English as a Foreign Language (EFL) is taught. However, there is still little research on how pre-service teachers use digital tools when facing serious material and geographic challenges. This study looks at the real experiences of pre-service English teachers at a rural private Islamic college in South Sumatra, Indonesia, as they used GenAI tools during their micro learning and teaching practicum. Using a hermeneutic phenomenological approach based on van Manen’s framework, data were gathered from structured, open-ended written reflections by all four students in the specialized track. The analysis found four main themes: (1) a shift in teaching beliefs from grammar-focused methods to Communicative Language Teaching (CLT); (2) the use of GenAI as a support tool alongside hands-on, non-digital adaptations, showing a digital divide within the group; (3) the Macro-Micro Paradox, where technical lesson planning with GenAI made classroom challenges more visible, especially due to teacher anxiety and student passivity; and (4) a change in professional identity from strict knowledge transmitters to flexible, empathetic facilitators. The study introduces the Macro-Micro Paradox, showing that while GenAI helps with lesson planning, it cannot solve the social and emotional challenges of real classroom engagements. These results indicate that teacher education programs should be re-examined to include digital empathic and technical skills, and that policy support is needed for underfunded faith-based institutions in the Global South.